Epistemic Fundamentals of Qualitative and Quantitative Research: Consensus and Dissensus - Sánchez Flores, Fabio Anselmo (2019)
This article analyzes the main characteristics of research with a quantitative and qualitative approach, contrasting its differences and pointing out their historical and epistemic similarities as well as methodological and procedural. Likewise, its pertinence is defined depending on the subject of study and the discipline—scientific, proto-scientific or human—in which it is framed, providing guidelines for the selection of one approach or the other, or of both—mixed research—through the estimation of its advantages and disadvantages for scientific research. On the other hand, it highlights the importance of establishing communication and integration channels between the corresponding cognitive approaches, far from the conceptions that seek to find dissent rather than consensus, thus contravening the value of studies with a mixed or complementary approach, which would be an alternative to the previous ones, but not for that reason superior or always necessary.